Variable use of standards-based IOS enabling technologies in Australian SMEs: an examination of deliberate and emergent decision making processes. Issue 2 (1st March 2017) - Power, Damien; Gruner, Richard L.
Abstract: Use of inter-organizational systems (IOS) is widely recognized as pivotal to organizational success. However, the nature of decision making processes regarding the adoption and use of IOS-enabling technologies has received little research attention. The authors explore approaches to decision making relating to SMEs' use of these technologies and outline the drivers and implications of such decision making. Data were collected through two crosssectional surveys and multiple case studies. The surveys allowed for the identification of two groups of three SMEs each—the first group increased and the second group decreased the use of IOS-enabling technologies over time. This identification provided the context of strategic change or transition in the use of these technologies over time. The study's results challenge widely held assumptions about the performance benefits of higher-level, deliberate planning over functional-level, emergent decision making regarding SMEs' technological choices. Results also show that SME managers mainly use flexible IOS technology adoption and implementation strategies to promote organizational performance. Further, two main factors drive flexible decision making: a lack of managerial power and a lack of financial resources. Overall, the study offers insights into the link between IOS-enabling technology use and organizational strategy, and advances research concerning the contingencies influencing SMEs' decision making in this context.